If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+y/6=-13
We simplify the equation to the form, which is simple to understand
2+y/6=-13
Simplifying:
2 + 0.166666666667y=-13
We move all terms containing y to the left and all other terms to the right.
+ 0.166666666667y=-13-2
We simplify left and right side of the equation.
+ 0.166666666667y=-15
We divide both sides of the equation by 0.166666666667 to get y.
y=-90
| (x+2)(5x-4)=0 | | 2x^2=3+9x | | 7x-6=3x+14 | | 10e+2e-9=39 | | 10x-15=6x+30 | | 4x+6=91 | | (x-8)(5x-4)=0 | | 4y+12=6y+14 | | 12j=16j(j-8) | | (3w-4)(4w+6)= | | 3x-2(-5x+3)=72 | | 7+2(7)=30 | | h=0.5s-5 | | 20-5w=60 | | 6-10m=-54 | | 8-3p=-14 | | X+3y=-15 | | 2v^2-14v=0 | | 2+4n=-10 | | 1x-4x=6 | | 10=-5(3+w) | | 7-2n=5 | | 23x-16871=1000 | | 7(10w+1)= | | (x+2)(x-8)(5x-4)=0 | | 9xy^2+4y-13=0 | | (x-3)=-3x+33 | | 15x+9= | | 24=3-7x | | 2b+2=3p-7 | | 3x-2=2x+13 | | -12x+3=-8x-6 |